2013
DOI: 10.1007/s10847-013-0361-7
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and spectral studies of auto-assembled arrays of calix[4]arenequinhydrone charge-transfer complex on indium–tin oxide (ITO) glass

Abstract: A sensing materiel based on calix[4]arene molecules is electrochemically deposited on ITO electrode coated. A brown film was electrodeposited at a potential Eimp = –1.00 V versus SCE in acetonitrile solvent, however in dichloromethane solvent, a bluish film auto-assembled on the ITO electrode coated at a potential Eimp = −0.65 V versus SCE. Both films are subsequently analyzed by cyclic voltammetry and UV–Vis spectroscopy. This investigation shows that in acetonitrile solvent, the charge-transfer complex, cali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…Hydroquinone and benzoquinone form a deep purple C-T complex by simple grinding (see Supplementary Figure 14; crystals of the complex are green). Calix[4]arenequinones 25 were also eventually found to form quinhydrone-type complexes possessing a broad electronic absorption characteristic of C-T in their electronic absorption spectra 26,27 . However, the physical properties of C-T interactions between phenols and hemiquinones have not been previously reported, and therefore we set about determining the origin of the observation in the series 2 compounds.…”
Section: Discussionmentioning
confidence: 99%
“…Hydroquinone and benzoquinone form a deep purple C-T complex by simple grinding (see Supplementary Figure 14; crystals of the complex are green). Calix[4]arenequinones 25 were also eventually found to form quinhydrone-type complexes possessing a broad electronic absorption characteristic of C-T in their electronic absorption spectra 26,27 . However, the physical properties of C-T interactions between phenols and hemiquinones have not been previously reported, and therefore we set about determining the origin of the observation in the series 2 compounds.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that calixarene and resorcinarene macrocycles, and other molecules containing both quinone and hydroquinone or hemiquinone/phenol groups undergo intramolecular charge transfer (C-T) interactions. 22,34,35 Thus, we speculate that reduction in electron density on phenol groups caused by their proximity to electron decient hemiquinones in the same molecule eliminates formation of phenoxyl radical in rccc-1[Ox 2 ] while two phenol groups of rctt-1[Ox 1 ] are sufficiently remote (see Fig. 3(a)) from its hemiquinone that reaction with singlet oxygen is permitted.…”
Section: Singlet Oxygen Photosensitizationmentioning
confidence: 99%
“…The electrochemical behavior of these films on indium tin oxide electrodes was also investigated. 7 More recently, Ogoshi and co-workers have pushed the field forward using pillar[n]arenes, 8 a family of macrocyclic hosts (see Figure 1B) that was initially prepared in their laboratory and has attracted considerable attention in the last decade. Primarily working with pillar [6]arenes, they partially oxidized them to generate macrocycles containing both hydroquinone and benzoquinone units, which self-assemble into fibrous materials.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The same group has described the formation of calix–quinhydrone complexes, formed by the interactions of calixarenes containing quinone units with their reduced counterparts, giving rise to solvatochromic, self-organized films. The electrochemical behavior of these films on indium tin oxide electrodes was also investigated …”
Section: Introductionmentioning
confidence: 99%